2019
DOI: 10.1111/1750-3841.14852
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical and Microbiological Quality of Lightly Processed Salmon (Salmo salar L.) Stored Under Modified Atmosphere

Abstract: Low-temperature cooking, such as sous vide, has become a favored method for processing seafood. For this method to be applicable for retail products, combinations with other processing steps are needed to keep the products safe and durable while maintaining high quality. The present experiments were designed to investigate the influence of low-temperature treatment (40, 50, or 60°C) in combination with various packaging technologies (modified atmosphere [MA] or soluble gas stabilization [SGS]) on both the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…However, no effect was shown on fillet yellowness (b* > 0) (p > .56). The slightly lighter and more reddish color observed on salt-injected fillets was unexpected because heat-induced flesh-lighting caused by the denaturation of muscle proteins (Abel et al, 2019;Lerfall et al, 2018;Ovissipour et al, 2017) was expected to equalize color differences resulting from the smoking technology.…”
Section: Colorimetric and Textural Propertiesmentioning
confidence: 99%
“…However, no effect was shown on fillet yellowness (b* > 0) (p > .56). The slightly lighter and more reddish color observed on salt-injected fillets was unexpected because heat-induced flesh-lighting caused by the denaturation of muscle proteins (Abel et al, 2019;Lerfall et al, 2018;Ovissipour et al, 2017) was expected to equalize color differences resulting from the smoking technology.…”
Section: Colorimetric and Textural Propertiesmentioning
confidence: 99%
“…Previous research has described the influence of these factors on the quality (including the nutritional value, and sensory and microbiological quality) of different fish species [17][18][19]. Previous studies [9,16,[20][21][22][23][24] discuss salmon prepared by sous-vide, but in a different context than our study. Our recent results [24] revealed that low parameter sous-vide processes resulted in products with similar characteristics to raw salmon, while higher parameters achieve a high intensity cooked fish odor and flavor without significant deterioration in texture.…”
Section: Introductionmentioning
confidence: 61%
“…Similarly, Picouet, Cofan-Carbo, Vilaseca, Ballbè & Castells [41] reported an increase of the total viable count (TVC) and Enterobacteriaceae count after sous-vide processing of salmon (50 • C, 20 min). Abel et al [16] demonstrated that a low temperature (40 or 50 • C) process still allows for obtaining an inhibitory effect on Listeria spp.…”
Section: Microbiological Qualitymentioning
confidence: 99%
See 2 more Smart Citations